The Spiritual Journey and The Unitive Experience: A Semantic Analysis on the Concept of Wuṣūl in Six Kitāb of Ṭarīqah Qādiriyyah wa Naqshabandiyyah - Aris Widodo (Universitas Islam Negeri Mataram, 2016)
One of the striking issues that beset human beings is how to have the encounter with God, to whom they worship. Therefore, some of them design a roadmap of spiritual journey to have the encounter. An Islamic Sufi order, Ṭarīqah Qādiriyyah wa Naqshabandiyyah (TQN) have done so. This article tries to deal with the three ways of spiritual journey that will enhance human beings to arrive (wuṣūl) at God as explained in six books of the TQN. Besides, using semantic approach, this study also endeavors to unearth the concept of wuṣūl encapsulated in the three ways of the spiritual journey. Apart from that, this article takes into account as well whether the concept of wuṣūl in the TQN as a unitive experience refers to waḥdah al-wujūd or wahdah al-shuhūd. By comparing the indicators, this article comes to the conclusion that the concept of wuṣūl in the TQN refers to the waḥdah al-shuhūd. DOI: http://dx.doi.org/10.20414/ujis.v20i2.811